A Comprehensive Analysis of Goods and Services Tax (GST) in India - Nayyar, Anand; Singh, Inderpal (Indian Journal of Finance, 2018)
The Goods and Services Tax (GST), implemented on July 1, 2017, is regarded as a major taxation reform till date implemented in India since independence in 1947. GST was planned to be implemented in April 2010, but was postponed due to political issues and conflicting interest of stakeholders. The primary objective behind development of GST is to subsume all sorts of indirect taxes in India like Central Excise Tax, VAT/Sales Tax, Service tax, etc. and implement one taxation system in India. The GST based taxation system brings more transparency in taxation system and increases GDP rate from 1% to 2% and reduces tax theft and corruption in country. The paper highlighted the background of the taxation system, the GST concept along with significant working, comparison of Indian GST taxation system rates with other world economies, and also presented in-depth coverage regarding advantages to various sectors of the Indian economy after levising GST and outlined some challenges of GST implementation.